Keen competition in East-West trade - Alfred E. Schulz (Intereconomics, 1967)
Parallel to the economic growth and the increase of the living standards in the Eastern bloc the import requirements of its member countries are rising, too. For this reason all Western industrial nations make increasing efforts to establish themselves in these markets with good future prospects or to maintain and extend traditional positions. However, trade between the East and the West is more difficult than among Western industrial States. The differing control of the economies causes a multitude of difficulties in opening new business connections and for transactions. These impediments are still increased by differing conceptions of the world. INTERECONOMICS interviewed Herr Alfree E. Schulz, Member of the Board of Directors of DEMAG Aktiengesellschaft, on the present situation of the West Germon Eastern trade.
Keywords: 330; Interview